2023
DOI: 10.3390/ph16091298
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Personalized In Silico Prediction of Treatment Efficacy in Cardiovascular and Chronic Kidney Disease: A Proof-of-Concept Study

Mayra Alejandra Jaimes Campos,
Iván Andújar,
Felix Keller
et al.

Abstract: (1) Background: Kidney and cardiovascular diseases are responsible for a large fraction of population morbidity and mortality. Early, targeted, personalized intervention represents the ideal approach to cope with this challenge. Proteomic/peptidomic changes are largely responsible for the onset and progression of these diseases and should hold information about the optimal means of treatment and prevention. (2) Methods: We investigated the prediction of renal or cardiovascular events using previously defined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…In a recent study, urinary peptides were shown to predict responses to BP medication [47]. Using the identified peptide changes, along with the predicted impact of intervention on urinary peptides [5], might help personalize intervention and ultimately select the most appropriate therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, urinary peptides were shown to predict responses to BP medication [47]. Using the identified peptide changes, along with the predicted impact of intervention on urinary peptides [5], might help personalize intervention and ultimately select the most appropriate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…T he increasing burden of chronic diseases indicates the need for noninvasive, easily accessible, stable, and cost-effective biomarkers. The field of urinary proteomics/peptidomics has developed extensively and consistently over the past two decades, with a focus on kidney and cardiovascular diseases [1][2][3][4][5][6]. Thousands of proteins present in the human body are ultimately degraded by ubiquitous proteolytic enzymes, resulting in the generation of protein fragments, that is, peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, in a recent manuscript urinary peptides were shown to predict the response to blood pressure medication 51 . Using the identified peptide changes along with the predicted impact of intervention on urinary peptides 52 might help towards personalizing intervention and ultimately selecting the most appropriate therapy.…”
Section: Discussionmentioning
confidence: 99%

Association of urinary peptides with hypertension

Mavrogeorgis,
Kondyli,
Mischak
et al. 2023
Preprint
Self Cite
“…These peptides serve as early indicators of the likelihood of mortality, providing valuable insights into the underlying pathophysiological mechanisms driving adverse outcomes in COVID-19 patients. By leveraging these predictive biomarkers, healthcare professionals can proactively identify individuals at elevated risk of mortality and implement targeted interventions aimed at mitigating this risk, thereby potentially altering the trajectory of the disease course, like already showed for chronic kidney and heart diseases 8 .…”
Section: Main Textmentioning
confidence: 99%